Diallyl disulfide and diallyl trisulfide in garlic as novel therapeutic agents to overcome drug resistance in breast cancer - RamaRao Malla; Rakshmitha Marni; Anindita Chakraborty; Mohammad Amjad Kamal (Elsevier, 2022)
Breast cancer is one of the leading causes of cancer-related deaths in women worldwide. It is a cancer that originates from the mammary ducts and involves mutations in multiple genes. Recently, the treatment of breast cancer has become increasingly challenging owing to the increase in tumor heterogeneity and aggressiveness, which gives rise to therapeutic resistance. Epidemiological, population-based, and hospital-based case-control studies have demonstrated an association between high intake of certain Allium vegetables and a reduced risk in the development of breast cancer. Diallyl disulfide (DADS) and diallyl trisulfide (DATS) are the main allyl sulfur compounds present in garlic, and are known to exhibit anticancer activity as they interfere with breast cancer cell proliferation, tumor metastasis, and angiogenesis. The present review highlights multidrug resistance mechanisms and their signaling pathways in breast cancer. This review discusses the potential anticancer activities of DADS and DATS, with emphasis on drug resistance in triple-negative breast cancer (TNBC). Understanding the anticancer activities of DADS and DATS provides insights into their potential in targeting drug resistance mechanisms of TNBC, especially in clinical studies.